(3GdJbQjH aj CSQGQ GdJQcjHs - (3GdLdOcqj, YR GdOjf, Ydj Hf eMeO Hf CjOeQ, J HYO (B742 (3g`s
(3ChdgG (B:s
(3HSe Gddg(B...(3bGd GdLdOcj aj GdKGdK ef GdJbQjH aj(B...s
(3BNQgG (B:s
...(3eG bOefG PcQg ajeG eVi ef cJGHfG gPG ajLH Cf JJCedg HacQI UGajI hbQjMI LjOI(B...(3hHGddg GdJhajb(B...(3Je GdcJGHs
(3JHUQI GdYfhGf (B:s
(3GdJbQjH aj CSQGQ GdJQcjHs
(3JHUQI GdeDda (B:s
(3hbO GNJda aj GSeg abjd(B: (3CjOeQ Hf Ydjs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B:(3L(B5(3,U(B5s
Keywords: (3GdcjejGA hGdWHjYjGJs